Physicality as a psychological phenomenon - Ilyasova, Katherine (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article is devoted to the problem of corporeality as a psychological phenomenon. The problem of the human body and physicality is affected in many areas of psychology. The psychology of corporeality is not a scientific research. We study the genesis of the concept of "body" in works of domestic and foreign researchers. Particular attention needs to be paid to the analysis of factors influencing the perception of one’s own physicality. Corporeality is understood as a sociocultural phenomenon — the body of a person, having social and cultural features, is transformed under the influence of social and cultural factors. The connection between corporeality and human self-evaluation is proved. The article analyzes the psychology of corporeality in the historical aspect and from the standpoint of various scientific approaches. It is noted that in modern psychological studies there is a tendency to differentiate the consideration of various aspects of physicality. A theoretical analysis of modern psychological researches in the field of physicality is conducted. In the age of globalization without borders, and under the conditions of socio- cultural space virtualization, body becomes an apotheosis of eclecticism, merging together all that had seemed incompatible. On the basis of empirical research, the level of satisfaction with the own body of clients of cosmetologists and medical institutions is investigated. Article presents the results of methodological and empirical analysis of the satisfaction with body. Results show that body image is a category engendered and determined mostly by psychological factors. Body image may have a significant influence on the human well-being. Article describes the results of the study of the cosmetology institutions client satisfaction of their own body. Prospects for further research are identified.